Can sprint skiing on an indoor track predict on-snow skate sprint performance in competitive skiers? - Willis, S.; Heil, D. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: Field measures of roller skiing have previously been shown to correlate highly with cross-country skiing performance. However, use of an indoor running track for roller ski performance testing or training has not been described in the research literature. The purpose of this study was to determine if skate sprint roller skiing performance on an indoor track could accurately represent on-snow skate sprint skiing performance.